Peripheral Venous Waveform Analysis for Detecting Hemorrhage and Iatrogenic Volume Overload in a Porcine Model. Issue 4 (October 2016) - Hocking, Kyle M.; Sileshi, Ban; Baudenbacher, Franz J.; Boyer, Richard B.; Kohorst, Kelly L.; Brophy, Colleen M.; Eagle, Susan S.
ABSTRACT: Background: Unrecognized hemorrhage and unguided resuscitation is associated with increased perioperative morbidity and mortality. The authors investigated peripheral venous waveform analysis (PIVA) as a method for quantitating hemorrhage as well as iatrogenic fluid overload during resuscitation. Methods: The authors conducted a prospective study on Yorkshire Pigs (n = 8) undergoing hemorrhage, autologous blood return, and administration of balanced crystalloid solution beyond euvolemia. Intra-arterial blood pressure, electrocardiogram, and pulse oximetry were applied to each subject. Peripheral venous pressure was measured continuously through an upper extremity standard peripheral IV catheter and analyzed with LabChart. The primary outcome was comparison of change in the first fundamental frequency ( f 1 ) of PIVA with standard and invasive monitoring and shock index (SI). Results: Hemorrhage, return to euvolemia, and iatrogenic fluid overload resulted in significantly non-zero slopes of f 1 amplitude. There were no significant differences in heart rate or mean arterial pressure, and a late change in SI. For the detection of hypovolemia the PIVA f 1 amplitude change generated an receiver operator curves (ROC) curve with an area under the curve (AUC) of 0.93; heart rate AUC = 0.61; mean arterial pressure AUC = 0.48, and SI AUC = 0.72. For hypervolemia the f 1 amplitude generated an ROC curve with an AUC of 0.85, heart rate AUC = 0.62, mean arterial pressure AUC = 0.63, and SI AUC = 0.65. Conclusions: In this study, PIVA demonstrated a greater sensitivity for detecting acute hemorrhage, return to euvolemia, and iatrogenic fluid overload compared with standard monitoring and SI. PIVA may provide a low-cost, minimally invasive monitoring solution for monitoring and resuscitating patients with perioperative hemorrhage.